Polishing surgical metal pieces, granulomatosis and mineralogical analysis - Catinon, Mickaël; Chemarin, C.; Roux, E.; Cavalin, C.; Rosental, P.-A.; Thivolet-Bejui, F.; Vincent, M. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2016)
This report describes the case of a 44-year-old man with pulmonary nodules whose histological analysis initially suggested tuberculosis. The Mycobacterium tuberculosis (MT) culture was negative and a questionnaire revealed a professional activity of brushing and polishing surgical instruments without any protection for 7 years. A mineralogical analysis by optical and electron microscopy was performed on both a healthy lung tissue biopsy and a lung nodule in a paraffin block. Electron microscopy analysis revealed the presence of metal particles (iron oxide, titanium oxide, aluminum oxide and steel) in both samples. This study suggests that mineralogical analysis combined with a questionnaire on dust exposure could help redirect the diagnosis of a dust-related disease.